THE RELEVANCE OF IBNU MISKAWAIH'S THOUGHTS ON CHARACTER EDUCATION IN THE CONTEXT OF CONTEMPORARY SOCIAL MEDIA - Fajar Rahman; Bahtiar Siregar; Elsa Padia; Ulil Amri; Kiki Hardini (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The purpose of this research is to examine how Ibn Miskawayh’s thoughts on moral education influence the management of moral challenges in the current social media era. Various ethical issues such as cyberbullying, the spread of hoaxes, and the lack of politeness in communication have emerged alongside the increase in digital platform usage, indicating a decline in digital morals. This study is a qualitative research using the library research method. The primary data are drawn from Ibn Miskawayh’s seminal work, Tahdhib al-Akhlaq, which is analyzed using content analysis and descriptive-philosophical methods. The results show that Ibn Miskawayh’s concept of moral education remains relevant as a foundation for digital ethics through three main pillars: first, the concept of al-wasat (moderation) which trains social media users to be wise and proportional in consuming information; second, the strengthening of cognitive power (al-quwwah al-nathiqah) to filter negative content; and third, the formation of character based on internal self-control to achieve justice (‘adalah) when interacting in virtual public spaces. The conclusion of this research confirms that Ibn Miskawayh’s thoughts provide a curative and preventive framework for building a more civilized and ethical digital ecosystem.